2015
DOI: 10.1371/journal.pone.0122229
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Induced Transdifferentiation of RPE Cells is Mediated by TAK1

Abstract: Background and AimProliferative vitreoretinopathy (PVR) is an active process that develops as a complication upon retinal detachment (RD), accompanied by formation of fibrotic tissue. The main cells involved in the development of fibrotic tissue during PVR are the retinal pigment epithelial (RPE) cells. The RPE cells undergo epithelial-mesenchymal transition (EMT) which leads to complex retinal detachment and loss of vision. Transforming growth factor-β1 (TGF-β1) is considered as the main player in the EMT of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
4
40
1
2
Order By: Relevance
“…In the posterior eye, they are the likely causative factor behind the EMT of the RPE, a process that includes marked structural and functional alterations such as loss of the outer blood-retina barrier, reduced expression of RPE-characteristic genes, upregulation of αSMA and change from a cuboidal to a more spindle-shaped phenotype. Quite comparable changes as observed here in vivo have been reported for TGF-β-treated cultured RPE cells from various mammalian species (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Jun and Joo 2016;Tamiya and Kaplan 2016;Dvashi et al 2015;Yang et al 2016;Chen et al 2014). Overall, there is strong evidence that TGF-β signaling is among the most potent inducers of EMT in numerous epithelial cell types in and outside the eye (Miettinen et al 1994;Saika et al 2004;Roberts et al 2006;Thiery et al 2009;Thiery and Sleeman 2006;Kalluri and Neilson 2003;Guarino et al 2009;Hales et al 1994;Xu et al 2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the posterior eye, they are the likely causative factor behind the EMT of the RPE, a process that includes marked structural and functional alterations such as loss of the outer blood-retina barrier, reduced expression of RPE-characteristic genes, upregulation of αSMA and change from a cuboidal to a more spindle-shaped phenotype. Quite comparable changes as observed here in vivo have been reported for TGF-β-treated cultured RPE cells from various mammalian species (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Jun and Joo 2016;Tamiya and Kaplan 2016;Dvashi et al 2015;Yang et al 2016;Chen et al 2014). Overall, there is strong evidence that TGF-β signaling is among the most potent inducers of EMT in numerous epithelial cell types in and outside the eye (Miettinen et al 1994;Saika et al 2004;Roberts et al 2006;Thiery et al 2009;Thiery and Sleeman 2006;Kalluri and Neilson 2003;Guarino et al 2009;Hales et al 1994;Xu et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Since in culture conditions transforming growth factor-β (TGF-β) signaling has been reported to be a potent mediator of EMT in RPE cells (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Chen et al 2014;Tamiya and Kaplan 2016;Dvashi et al 2015;Jun and Joo 2016;Yang et al 2016), we studied the retinal phenotype of βB1-TGF-β1 mice, a transgenic mouse strain with an ocular overexpression of active TGF-β1 (Flügel-Koch et al 2002). Here, we show that the RPE of βB1-TGF-β1 mice undergoes an EMT, a process that becomes manifest after birth.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study demonstrated that the incidence is closely related Previous studies show that PVR formation is closely related to various cytokines that not only promote cell chemotaxis, migration, and aggregation, but also help regulate RPE cell differentiation and construction of the extracellular matrix [16][17][18]. EGF is a small molecule peptide growth factor secreted by platelets that can promote multiple cell division in vivo [19].…”
Section: Discussionmentioning
confidence: 70%
“…[27][28][29][30] However, most in vitro studies used exogenously applied TGFb to activate cellular pathways leading to EMT. 24,[31][32][33] Assays conducted in the current study were performed without addition of exogenous TGFb, yet the cells were able to respond to wounding by activating EMT. The three TGFb isoforms encoded by the human genome 34 have distinct and overlapping functions during wound healing.…”
Section: Discussionmentioning
confidence: 99%